Evaluation of potato zero tillage and mulching technologies under maize cropping system in Imenti South, Meru County, Kenya - Agili, S.; Munda, E.; Njagi, I.; Kagete, E.; Amboga, S.; Wanyoike, T.; Njoroge, P.; Nyaguthie, M.; Muriithi, G. (2025)
This study evaluates the performance of potato zero tillage and maize stover mulching technologies under a maize-based cropping system in Imenti South, Meru County, Kenya. Results from two contrasting rainy seasons show that zero tillage combined with an optimal mulch thickness of 20 cm significantly increases marketable potato yield, improves soil moisture retention, and stabilizes production under climatic stress. The findings demonstrate that conservation agriculture practices can enhance productivity, resilience, and resource-use efficiency in smallholder potato systems, providing an evidence-based pathway for climate-smart and regenerative agriculture in Eastern Africa.